1998
DOI: 10.1074/jbc.273.13.7210
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Transactivation Function of the Transcription Factor Encoded by the Eye Developmental Gene PAX6

Abstract: PAX6 is a transcription activator that regulates eye development in animals ranging from Drosophila to human. The C-terminal region of PAX6 is proline/serine/ threonine-rich (PST) and functions as a potent transactivation domain when attached to a heterologous DNAbinding domain of the yeast transcription factor, GAL4. The PST region comprises 152 amino acids encoded by four exons. The transactivation function of the PST region has not been defined and characterized in detail by in vitro mutagenesis. We dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 49 publications
(48 reference statements)
2
72
0
1
Order By: Relevance
“…Pax-6 contains an unusually long transactivation domain (TAD) suggesting that it could provide interaction surfaces for several cofactors [48,49]. Synergistic interaction of Pax-6 and Cdx-2/3 with the p300 coactivator has been demonstrated [43] but it is not likely that Pax-4 inhibits Pax-6 mediated transcriptional activation by interfering with p300 binding because Cdx-2/3-induced transcription is not impaired by Pax-4.…”
Section: Discussionmentioning
confidence: 99%
“…Pax-6 contains an unusually long transactivation domain (TAD) suggesting that it could provide interaction surfaces for several cofactors [48,49]. Synergistic interaction of Pax-6 and Cdx-2/3 with the p300 coactivator has been demonstrated [43] but it is not likely that Pax-4 inhibits Pax-6 mediated transcriptional activation by interfering with p300 binding because Cdx-2/3-induced transcription is not impaired by Pax-4.…”
Section: Discussionmentioning
confidence: 99%
“…The PDs of other genes of the Pax family, the Pax2, Pax3, and the binding sequence of Pax-5 (BSAP), and Pax6 proteins can recognize similar DNA sequences (12, 34 -39). Our earlier studies showed that the transactivation function is distributed throughout the PST region (40). Although the involvement of PAX6 in ocular development is well known (41,42), identification of target genes of PAX6 has been hindered by two factors.…”
mentioning
confidence: 99%
“…Functional studies using PAX6 missense mutations with observed developmental defects are useful in understanding the mechanism of PAX6 function. Missense mutations in the DNA-binding domains of PAX6 may cause failure to properly recognize binding sites in the target genes, resulting in partial or complete loss of protein function (40,(47)(48)(49).…”
mentioning
confidence: 99%
“…21 Furthermore, in the C-terminal part of the protein there is a proline, serine and threonine rich (PST) domain of 152 amino acids 3 which resembles the activation domain of transcription factors CTF-1 (CAAT-box binding transcription factor) 22 and Oct2, 23 and has been shown to possess transcriptional activity in vitro. 12,24,25 Quail Pax-6 has been shown to transactivate its own promoter, 26 and Pax-6 from mouse, chicken and guinea pig was shown to be involved in transcriptional regulation of crystallin genes. 27 Pax-6 belongs to the Pax family of developmental control factors 28 all possessing the paired domain originally identified in the Drosophila melanogaster segmentation gene paired.…”
Section: Introductionmentioning
confidence: 99%